Learning from the Field: Understanding Philanthropy’s Role in Supporting Higher Education’s Recovery from the Pandemic (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
The coronavirus has magnified existing racial injustices and educational inequities. Philanthropy will play a key role in facilitating higher education’s recovery from the pandemic, but its relationship with the field needs to evolve so it can enact a more equitable and sustainable future. Informed by 30 responses from grantee partners (e.g., college leaders, scholars, research organizations, and community-based nonprofits), one foundation is on a journey to ensure that its relationships with the field are grounded in a deep understanding of partners’ needs during the pandemic and their continued service to America’s most marginalized college students. This essay features what the foundation has learned as a result of its grantees’ persistence and the actions it will undertake to further support educational equity.